The Conduct Of Marriage Contracts In Mosques Fron Perspective Of Syafii Jurisprudence - Haikal, Muhammad (Jurnal Al-Fikrah, 2024)
This study addresses a controversy sparked by a religious figure in Aceh who equated marriages conducted in mosques with Christian weddings in churches, leading to significant community debate. The research investigates the perspective of the Syafi'i school of jurisprudence on conducting marriages in mosques. Utilizing a qualitative approach with library research methods, the study concludes that scholars of the Syafi'i school permit the practice of conducting marriages in mosques.